Applications of Nachbin’s Theorem concerning Dense Subalgebras of Differentiable Functions - Kashimoto, Marcia Sayuri (Trends in Computational and Applied Mathematics, 2018)
In this paper, we give some applications of Nachbin’s Theorem to approximation and interpolation in the the space of all k times continuously differentiable real functions on any open subset of the Euclidean space.